Management of pure medial orbital wall fracture with autogenous bone graft - Pereira, Rodrigo Dos Santos [UNESP]; Jorge-Boos, Fernanda Brasil Daura [UNESP]; Hochuli-Vieira, Eduardo [UNESP]; Da Rocha, Hernando Valentim; Homsi, Nicolas; De Melo, Willian Morais (Wolters Kluwer, 2013)
The orbit is an irregular conical cavity formed from 7 bones including the frontal, sphenoid, zygomatic, maxillary, ethmoid, lacrimal, and palatine bones. Fractures of the internal orbit can cause a number of problems, including diplopia, ocular muscle entrapment, and enophthalmos. Although muscle entrapment is relatively rare, diplopia and enophthalmos are relatively common sequelae of internal orbital fractures. Medial orbital wall fracture is relatively uncommon and represents a challenge for its anatomical reconstruction. In this context, autogenous bone graft has been the criterion standard to provide framework for facial skeleton and orbital walls. Therefore, it is possible to harvest grafts of varying size and contour, and the operation is performed through the bicoronal incision, which is the usual approach to major orbital reconstruction. Thus, this article aimed to describe a patient with a pure medial orbital wall fracture, and it was causing diplopia and enophthalmos. The orbital fracture was treated using autogenous bone graft from calvarial bone. The authors show a follow-up of 12 months, with facial symmetry and without diplopia and enophthalmos. In addition, a computed tomography scan shows excellent bone healing at the anterior and posterior parts of the medial orbital wall reconstruction. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Bone graft; Diplopia; Enophthalmos; Medial orbital wall fracture; Orbital fracture; Surgical management